Development of Comprehensive Parameter Measuring Machine for Precise RV Reducer - Qi Haoran; Wang Xiaoling; Zhang Lintao (Jixie chuandong, 2016)
A comprehensive parameter measuring machine for precise RV reducer is developed,which can measure the parameters of transmission error,backlash,stiffness and friction moment and so on. This machine mainly consists of mechanical structure design,measuring & control system and measuring software,which can acquire the parameters of RV reducer rapidly and accurately by a simply one-time clamping. The mechanical structure includes base,input & output components and mounting support. By using the FEA software Hypermesh 12. 0,the output shaft strength is analyzed,it is meeting the strength condition under the condition of output maximum torque of 2 000 N·m when measuring the backlash.